Men's Experiences of Violence in Intimate Relationships - Lien, Marianne Inéz
This open access book draws on a broad study on violence against men, from both male and female partners in Norway, to contribute to the research on intimate partner violence. It identifies similarities in men's experiences and backgrounds, including in their perceptions of their own victimisation. Marianne Inez Lien and Jørgen Lorentzen argue that the traditional gender power model should be modified and supplemented, and propose that we consider violence in terms of psychological supremacy, rather than in terms of femininity and masculinity. Men's Experiences of Violence in Intimate Relationships will appeal to students and scholars across a range of areas including criminology, sociology and family violence, and gender studies